2014
DOI: 10.1063/1.4876576
|View full text |Cite
|
Sign up to set email alerts
|

Interchannel coupling effects in the valence photoionization of SF6

Abstract: The complex Kohn and polyatomic Schwinger variational techniques have been employed to illustrate the interchannel coupling correlation effects in the valence photoionization dynamics of SF6. Partial photoionization cross sections and asymmetry parameters of six valence subshells (1t1g, 5t1u, 1t2u, 3eg, 1t2g, 4t1u) are discussed in the framework of several theoretical and experimental studies. The complex Kohn results are in rather good agreement with experimental results, indicative of the fact that the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…It was proposed 44 that the first step, i.e., strong field ionization involves contributions from multiple electronic channels, while the recombination step is influenced by resonant transitions due to the presence of autoionizing states and shape resonances trapping the recolliding electron for typically hundreds of attoseconds before recombination to the ground state occurs. The specific behavior observed for H15 and H17 was related to the presence of the 5t1u  t2g shape resonance in the A channel that dominates the harmonic emission in this spectral range, as shown by complex Kohn computations of valence PI total cross sections involving strong intercoupling effects 72 . The influence of resonances was then investigated using 2D-TDSE simulations for Ar atoms (see the supplementary information of 38 ), and it was found that they result in a structuring of the returning electron wavepacket and an increase of the perpendicular component of the dipole in the radiative recombination step of the HHG process.…”
Section: Molecular Polarimetry: An In Situ Tool For Polarization Analmentioning
confidence: 86%
“…It was proposed 44 that the first step, i.e., strong field ionization involves contributions from multiple electronic channels, while the recombination step is influenced by resonant transitions due to the presence of autoionizing states and shape resonances trapping the recolliding electron for typically hundreds of attoseconds before recombination to the ground state occurs. The specific behavior observed for H15 and H17 was related to the presence of the 5t1u  t2g shape resonance in the A channel that dominates the harmonic emission in this spectral range, as shown by complex Kohn computations of valence PI total cross sections involving strong intercoupling effects 72 . The influence of resonances was then investigated using 2D-TDSE simulations for Ar atoms (see the supplementary information of 38 ), and it was found that they result in a structuring of the returning electron wavepacket and an increase of the perpendicular component of the dipole in the radiative recombination step of the HHG process.…”
Section: Molecular Polarimetry: An In Situ Tool For Polarization Analmentioning
confidence: 86%
“…While simple single electron models or low dimensional models have been partially successful in explaining laser matter interactions, there have been several cases reported where a more elaborate description of electronic structure becomes important. Some of the examples include inter-channel coupling leading to an enhancement in high harmonic generation (HHG) from xenon [3], modification of angle resolved ionization yield of CO 2 [4] and photoionization cross-sections in SF 6 [5], enhancement in HHG due to participation of doubly excited states in beryllium [6], influence of nuclear motion [7], presence of conical intersections [8] and so on. All these instances need a more involved description of the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…SF6 is particularly interesting in the context of vibrational effects on shape resonances because photoionization from the valence and inner subshells are dominated by the presence of series of resonant peaks. There are many theoretical and experimental studies of the effects of shape resonances on the photoionization parameters of SF6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It has been confirmed from previous results that there are four prominent shape resonances with symmetries a1g, t1u, t2g, and eg in the photoionization spectra of the valence orbitals of SF6.…”
Section: Introductionmentioning
confidence: 72%
“…Owing to the significance of shape resonances in the photoionization process, sulphur hexafluoride has been the subject of many important studies in physics and chemistry for few decades [1][2][3][4][5][6][7][8][9][10][11][12]. Photoionization dynamics of valence and core subshells of SF6 is significantly affected by the shape resonances, occurring both below and above the ionization threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation